2017
DOI: 10.3390/jfmk2020017
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vibration as Physical Exercise and Therapy

Abstract: Abstract:Musculoskeletal vibration stimulation is the topic chosen for this review. The aim is to discuss this interesting, but poorly analyzed topic in the current literature in order to explain and help readers to better understand the effects of vibration used as an exercise intervention and therapy for muscle, bone, and cartilage tissues. The use of vibration stimulation for enhancing athletic performance and therapeutic use is considered an important matter of medical biology that has developed in the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Even if, in this case, the vibration has had a negative effect, this does not mean that vibrations always cause pain. The vibration of musculoskeletal structures could be an effective exercise intervention for reducing the negative effects of aging on bone, cartilage, muscles, and tendons, 9,10 but the type of vibration treatment (amplitude, frequency, and magnitude of the oscillations) should be personalized because the effect of vibration stimulus is very subjective; otherwise, this treatment would have no effect or, as in this case, deleterious effects 9,10 . The positive or negative effects of vibration exercise on the musculoskeletal system need to be better analyzed in order to verify its effectiveness on muscle strength, bone remodeling, and cartilage preservation.…”
Section: Case Reportmentioning
confidence: 99%
“…Even if, in this case, the vibration has had a negative effect, this does not mean that vibrations always cause pain. The vibration of musculoskeletal structures could be an effective exercise intervention for reducing the negative effects of aging on bone, cartilage, muscles, and tendons, 9,10 but the type of vibration treatment (amplitude, frequency, and magnitude of the oscillations) should be personalized because the effect of vibration stimulus is very subjective; otherwise, this treatment would have no effect or, as in this case, deleterious effects 9,10 . The positive or negative effects of vibration exercise on the musculoskeletal system need to be better analyzed in order to verify its effectiveness on muscle strength, bone remodeling, and cartilage preservation.…”
Section: Case Reportmentioning
confidence: 99%
“…Because of the potential positive effects, vibration has been used to treat musculoskeletal diseases as well as to increase athletic performance in humans. Work still needs to be done, however, to determine the accelerations and frequencies that are most beneficial . As discussed below , because the frequency, magnitude, and duration of exposure can determine if vibration will have negative, positive or no effects, animal models will be important in developing these therapeutic uses.…”
Section: Adverse Vibration Effects and Potential Benefits In Animals mentioning
confidence: 99%
“…Because of the varied nature of experimental design applied to WBV studies reported in the literature, it is challenging to determine which vibration protocol is likely to have the greatest benefit, adverse effects, or no effects at all. For example, in studies to use vibration exposure for promoting bone growth or maintenance, there were acceleration ranges between 2.94 and 29.43 m/s 2 , frequency ranges between 8 and 90 Hz, varied durations of exposure, as well as animal age and species . Higher magnitude WBV of 19.62 and 29.43 m/s 2 was only osteogenic in ovariectomized rats, (p316) whereas low magnitude vibration applied to osteoporotic (ovariectomized) rats at approximately 2 m/s 2 reversed some of the negative effects of osteoporosis and accelerated early peri‑implant osseointegration .…”
Section: Challenges In Animal Study Designmentioning
confidence: 99%
“…These impulses cause involuntary muscle contractions and recruit fast-twitch fibers that are mainly affected by age-induced muscle atrophy [56]. In the past few years, WBV was proposed as a mild approach to counteract sarcopenia and osteoporosis in the elderly [54]. Standing on an oscillating platform determines an improved response of the leg and postural muscles through the so-called tonic vibration reflex [57].…”
Section: Exercisementioning
confidence: 99%
“…Unfortunately, many forms of physical activity are either too intense or too monotonous for older adults to be maintained over a long period. Then, new exercise tools, such as whole-body vibration (WBV) and whole-body electromyostimulation (WB-EMS), are offered as alternative methods to increase or maintain muscle mass and function [53,54]. WB-EMS is known as an established skill primarily practiced as a local, passive application [55].…”
Section: Exercisementioning
confidence: 99%